Analisis Keterampilan Membaca Lanjutan Siswa Sekolah Dasar di Kelas III–A SD Negeri 064037 - Azzahra, Shadrina; Sitorus, Putri Aulia; Nasution, Ratiqa Balqis; Nadya, Laila; Hutasuhut, Naila Audiva (ANWARUL, 2023)
Advanced reading is a reading skill that is more complex and requires deeper understanding. Advanced reading skills are very important because they help a person to understand more complex information and broaden one's horizons. To improve advanced reading skills, one needs to practice beginning reading skills first. Beginning reading skills include the ability to recognize letters, read words, and read sentences. After the initial reading ability is well trained, a person can practice advanced reading skills by reading reading material that is more complex and requires a deeper understanding. One method that can be used to improve reading comprehension skills is the REAP (Read, Encode, Annotate, Ponder) method. This method involves four stages, namely reading, marking, writing, and pondering. This writing aims to find out to improve advanced reading skills in class III students of SD N 064037 advanced reading in high classes in order to improve reading skills in student learning in high classes & improve learning abilities. This research uses a rational approach method which was compiled based on the results of observation and study References. From the results of the study it can be concluded that the use of good and relevant strategies in advanced reading learning in high grades can affect effectiveness and can improve students' learning abilities.